2017
DOI: 10.1097/md.0000000000008483
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of the spinal cord in the evaluation of 3 patients with sensory neuronopathies

Abstract: Rationale:Sensory neuronopathy can be a devastating peripheral nervous system disorder. Profound loss in joint position is associated with sensory ataxia, and reflects degeneration of large-sized dorsal root ganglia. Prompt recognition of sensory neuronopathies may constitute a therapeutic window to intervene before there are irreversible deficits. However, nerve-conduction studies may be unrevealing early in the disease course. In such cases, the appearance of dorsal column lesions on spinal-cord MRI can help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Because large-fiber cell bodies are often also attacked, patients can have ataxia or reduced proprioception, hyporeflexia and abnormal nerve conduction study results, or somatosensory-evoked potentials. Magnetic resonance imaging may become useful …”
Section: Non–length-dependent and Patchy Presentationsmentioning
confidence: 99%
“…Because large-fiber cell bodies are often also attacked, patients can have ataxia or reduced proprioception, hyporeflexia and abnormal nerve conduction study results, or somatosensory-evoked potentials. Magnetic resonance imaging may become useful …”
Section: Non–length-dependent and Patchy Presentationsmentioning
confidence: 99%
“…Small case series have demonstrated non-enhancing, longitudinally extensive dorsal column lesions in patients with sensory neuronopathies, indicative of the degeneration of central afferent connections between the DRG and dorsal columns 198. A small case series of patients with CISP suggested that MRI abnormalities such as nerve root enlargement or enhancement may be useful diagnostically in patients with normal nerve conduction study results 125.…”
Section: Diagnostic Approachmentioning
confidence: 99%